Clinical outcomes among out-of-hospital cardiac arrest patients treated by extracorporeal cardiopulmonary resuscitation: The CRITICAL study in Osaka. (September 2022) - Okada, Yohei; Irisawa, Taro; Yamada, Tomoki; Yoshiya, Kazuhisa; Park, Changhwi; Nishimura, Tetsuro; Ishibe, Takuya; Kobata, Hitoshi; Kiguchi, Takeyuki; Kishimoto, Masafumi; Kim, Sung-Ho; Ito, Yusuke; et al.
Abstract: Aim: Extracorporeal cardiopulmonary resuscitation (ECPR) is performed in refractory out-of-hospital cardiac arrest (OHCA) patients, and the eligibility has been conventionally determined based on three criteria (initial cardiac rhythm, time to hospital arrival within 45 minutes, and age <75 years) in Japan. Owing to limited information, this study descriptively determined neurological outcomes after applying the three criteria among OHCA patients who underwent ECPR. Methods: This study conducted a post-hoc analysis of data from the Comprehensive Registry of Intensive Care for OHCA Survival (CRITICAL) study. This was a multi-institutional prospective observational study of OHCA patients in Osaka Prefecture, Japan. All adult (aged ≥18 years) OHCA patients with internal medical causes treated with ECPR between 1 July 2012 and 31 December 2019 were evaluated. We described one-month neurological favourable outcomes based on the three criteria (initial shockable, time to hospital arrival within 45 minutes, and age <75 years), and we compared them using the chi-square test. Results: Among 18, 379 patients screened from the CRITICAL study database, we included 517 OHCA patients treated by ECPR; 311 (60.2%) patients met all three criteria. Favourable neurological outcomes were as follows: patients meeting no or one criterion: 2.3% (1/43), those meeting two criteria: 8% (13/163), and those meeting all criteria: 16.1% (50/311) (P-value = 0.004). Conclusions: In this study, approximately 60% of patients treated by ECPR met the three criteria (initial shockable, time to hospital arrival within 45 minutes, and age <75 years), and the greater the number of criteria met, the better were the neurological outcomes achieved.